The mademoiselle alliance : a novel - Lester, Natasha, 1973- (Ballantine Books, 2025)
"In this stunning work of historical fiction, the New York Times bestselling author of The Paris Orphan brings to life the true story of Marie-Madeleine Fourcade, who led one of the largest and most effective resistance networks in France during World War II"--